2007
DOI: 10.1038/sj.bjc.6603985
|View full text |Cite
|
Sign up to set email alerts
|

ZD6474 reverses multidrug resistance by directly inhibiting the function of P-glycoprotein

Abstract: P-glycoprotein (P-gp) pumps multiple types of drugs out of the cell, using energy generated from ATP, and confers multidrug resistance (MDR) on cancer cells. ZD6474 is an orally active, selective inhibitor of the vascular endothelial growth factor receptor, epidermal growth factor receptor, and rearranged during transfection tyrosine kinases. This study was designed to examine whether ZD6474 reverses P-gp-mediated MDR in cancer cells. Here, we show that clinically achievable levels of ZD6474 reverse P-gp-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…Considering that amides are more stable than esters in metabolism, these synthetic amides derivatives are more promising candidates for antitumor agents than these esters derivatives. Adriamycin (ADR) and docetaxel (DOC) are selected as positive controls and they are both resisted by MCF-7/ADR significantly [25,26] and the results are consistent with this.…”
Section: Antiproliferative Activitysupporting
confidence: 65%
“…Considering that amides are more stable than esters in metabolism, these synthetic amides derivatives are more promising candidates for antitumor agents than these esters derivatives. Adriamycin (ADR) and docetaxel (DOC) are selected as positive controls and they are both resisted by MCF-7/ADR significantly [25,26] and the results are consistent with this.…”
Section: Antiproliferative Activitysupporting
confidence: 65%
“…Earlier reports indicated interaction of TKIs with ATPbinding domains of ATP-binding cassette (ABC) transportermediated multidrug resistance (MDR) proteins in cancer cells (43)(44)(45). Inhibition of P-glycoprotein (P-gp) activity (46) resulted in enhanced cytotoxic effects of multiple anticancer drugs by increasing accumulation of P-gp and ATP-binding cassette subfamily G member 2 (ABCG2) substrates (47,48). Earlier studies showed inhibition of hENT1-mediated activity in K562 cells by p38 MAPK inhibitors (29), and our current and previous results (32) indicate that another group of potential target proteins are hNTs.…”
Section: Discussionmentioning
confidence: 93%
“…As described before, MDR reversal agents against ABCB1 could be divided into three classes. Compounds belonging to the second class such as vandetanib and verapamil increasing the ATPase activity of ABCB1 in a dosedependent manner could inhibit the efflux of ABCB1 [Hamada and Tsuruo, 1988;Mi and Lou, 2007]. Herein, EFL1 stimulated the ATPase activity, increased intracellular accumulation of anticancer drugs and inhibited drug efflux of ABCB1.…”
Section: Discussionmentioning
confidence: 98%
“…Lapatinib was demonstrated to reverse ABCB1-mediated MDR and can increase the ATPase activities of the transporters at low concentrations [Dai et al, 2008]. It has been reported that vandetanib and verapamil can increase the ATPase activity of ABCB1 in a dose-dependent manner [Hamada and Tsuruo, 1988;Mi and Lou, 2007].…”
mentioning
confidence: 98%